A PANEL DATA EXPLORATION OF MACROECONOMIC FACTORS INFLUENCING THE OPTIMAL CAPITAL STRUCTURE OF THE INDIAN AUTOMOTIVE SECTOR - Sahoo, Tapas Kumar; Yarso, Awungshi; Das, Arijeet; Borah, Navajit; Gachuiwo, Happyson (Bangladesh Journal of Multidisciplinary Scientific Research, 2024)
Economic instability in emerging economies presents substantial challenges for firms, particularly in accessing debt funding, due to heightened perceived risk. This often results in a less favorable debt-to-equity ratio and complicates the overall composition of capital structure. Macroeconomic conditions play a pivotal role in influencing investor sentiment and risk perceptions, which in turn complicate capital structure decisions. This study aims to investigate the impact of various macroeconomic variables on the capital structure decisions of firms within the Indian automobile and automobile ancillary sectors over a comprehensive 17-year period from 2004 to 2020. They are utilizing secondary data collected from reputable sources like ProwessIQ, the Reserve Bank of India, and financial reports. The study employs various statistical tools, including descriptive statistics, correlation analysis, and dynamic panel data regression models, to analyze the data. The findings indicate that macroeconomic variables significantly shape the optimal capital structure decisions in the Indian automotive sector. Key variables such as the bank rate, GDP growth rate, inflation rate, and public debt substantially impact leverage ratios. For instance, an increase in the bank rate or public debt levels correlates with higher leverage ratios, suggesting that firms adjust their capital structures in response to changes in these macroeconomic indicators. This study provides valuable insights into the complex interplay between macroeconomic conditions and capital structure financing decisions. By highlighting the significant influence of these broader economic factors, the research underscores the necessity for firms, especially in emerging economies like India, to consider these determinants when making financial decisions. The findings thus contribute to a deeper understanding of capital structure dynamics in the face of macroeconomic challenges within the Indian automotive sector.JEL Classification Codes: G32, C58, E01.